Investigation of the Effect of Calibration Curves Obtained from Different Computed Tomography Devices on the Dose Distribution of Tomotherapy Plans - Hikmettin Demir; Osman Vefa Gül; Gül Kanyilmaz (Journal of Medical Physics)
Purpose: This study investigated the effect of Hounsfield units (HU)-relative electron density (RED) calibration curves obtained with devices from three different Computed Tomography (CT) manufacturers on dose distribution in Accuray Precision planning of patients with lung cancer. Methods: All CT data required for treatment planning system (TPS) were obtained using the Tomotherapy “cheese” phantom. HU RED calibration curves were created with images obtained from Siemens Somatom, GE Optima, and Toshiba Aquilion devices. The obtained calibration curve was extrapolated. CT images of lung cancer patients were acquired on a single device and treatment plans were created. The existing plans were recalculated using three calibration curves and the effect of the HU RED calibration curve on dose distribution was analyzed. Results: The results showed that different CTs did not produce significant dose differences in organ doses and PTV for Accuray TPS. Conclusions: Based on clinical judgment, images from different CT devices can be used in treatment planning.